The genome empowerment scale: An assessment of parental empowerment in families with undiagnosed disease. Issue 6 (8th October 2019) - McConkie‐Rosell, Allyn; Schoch, Kelly; Sullivan, Jennifer; Cope, Heidi; Spillmann, Rebecca; Palmer, Christina G.S.; Pena, Loren; Jiang, Yong‐Hui; Daniels, Nicole; Walley, Nicole; Tan, Khoon G.; ,; et al.
Abstract: While genomic sequencing (ES/GS) has the potential to diagnose children with difficult to diagnose phenotypes, the goal should be not only a diagnosis, but also to empower parents to seek next steps for their children and to emotionally manage the outcome, whether or not a diagnosis is secured. To help achieve this goal, objective measures are needed to assess the process of parental empowerment related to genome sequencing. We present the validity and reliability of the Genome Empowerment Scale (GEmS), developed using a healthcare empowerment theoretical model. To evaluate its psychometric properties, 158 parents of 117 children with an undiagnosed condition undergoing genomic sequencing completed the GEmS, measures for criterion validity and for depression and anxiety. Factor analysis resulted in a four factor solution: (a) meaning of a diagnosis; (b) emotional management of the process; (c) seeking information and support and (d) implications and planning. Reliability and validity analyses show that the GEmS has good psychometric properties. The inter‐relationships among the factors revealed a profile that may identify parents at risk for a poorer outcome who may benefit from targeted genetic counseling. The GEmS, an objective measure of parental genomic empowerment, can be utilized for future research and translational applications. Abstract :